Exploring the internationalisation of MBA programme in UK as part of the national strategy from the perspectives of Chinese students - Xie, Chun (2006)
The higher education sector in UK, famous for its high quality and internationally recognized qualifications, has been receiving attention from various stakeholders for decades. However, in the past several years, the stronger trend of internationalization and the ever more dependence of UK universities on China and other overseas student market have been revealed and discussed heatedly by people of all walks. The focus of the discussion of this dissertation will be on one important player in the higher education sector, the business school, as it is recognized by many as a cash cow for its host university. Therefore in the industry and literature review chapter, the significance of the HE sector for the whole national economy and export business of UK will be examined, then the contribution of the business schools to their host universities will be highlighted, leading to the revelation of the fact that in the national strategy of internationalization of UK's HE sector, business schools have a significant role to play. Then the issues in the internationalization of business schools will be discussed in detail, as Chinese students have constituted the largest proportion of the international student cohort in all UK universities and especially so in the business schools. The focus of the discussion will then be on the Chinese students in the MBA programme of the business school, as they are experiencing difficulty due to their unique cultural background and expressing dissatisfaction toward their MBA study in UK. At the same time, business schools have seen declines in the applications of their MBA programmes, leading to the commonly recognized cash cow in some business schools facing losses. The reasons behind all these phenomena will be examined and analyzed from the perspectives of multiple stakeholders, namely, first of all, the business schools, then the faculty, the international, and more specifically, Chinese students, and finally, the Western students. These factors are intertwined, producing a complicated picture to be imagined in the internationalized MBA programmes of UK business schools.